2002
DOI: 10.2151/jmsj.80.1395
|View full text |Cite
|
Sign up to set email alerts
|

Effective Factors in the Development of Deep Convective Clouds over the Wet Region of Eastern China during the Summer Monsoon Season.

Abstract: A two-dimensional cloud-resolving model, including a supply of sensible and latent heat fluxes from the surface, is used to study the development of deep convective clouds over a southern region far from the Meiyu front (wet region) of eastern China. Some deep convective clouds were observed during the latter half of the GAME/HUBEX IOP (GEWEX Asian Monsoon Experiment/Huaihe River Basin Experiment Intensive Observation Periods, GEWEX: Global Energy and Water Cycle Experiment) 1998, although there is less large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…It is very clear that a finer resolution run leads to early maximum of convection while a coarser resolution run leads to the late maximum with strong intensity. In the past study effective upward moisture transport was suggested to be important for initiation of the deep convection (Petch et al 2002;Shinoda and Uyeda 2002). In the current study, efficiency of the vertical moisture transport by the grid-scale and subgrid-scale vertical motion is one of the important processes which may cause the phase difference.…”
Section: Factors Responsible For the Resolution Dependencymentioning
confidence: 71%
“…It is very clear that a finer resolution run leads to early maximum of convection while a coarser resolution run leads to the late maximum with strong intensity. In the past study effective upward moisture transport was suggested to be important for initiation of the deep convection (Petch et al 2002;Shinoda and Uyeda 2002). In the current study, efficiency of the vertical moisture transport by the grid-scale and subgrid-scale vertical motion is one of the important processes which may cause the phase difference.…”
Section: Factors Responsible For the Resolution Dependencymentioning
confidence: 71%
“…There are many previous studies showing that these kinds of thunderstorms usually develop in the summertime over landmasses [e.g., Kingsmill and Wakimoto, 1991;Shinoda and Uyeda, 2002;Shusse and Tsuboki, 2006;Case et al, 2008]. It is also plausible that soil moisture over the heated surface may significantly influence the evolution of air mass thunderstorms and the depth of the mixed boundary layer can influence the structure of the thunderstorms [McCaul and Cohen, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the meteorological operational network of the China Meteorological Administration (CMA), whose observational frequency was improved more than usual, was also operated. The important point of this experiment is to have placed the Doppler-radar network near the coastline, rather than inland (Huaihe River Basin) where the first Doppler radar observation was carried out during the Baiu seasons of 1998 and 1999, under the GAME/HUBEX 1 project (e.g., Maesaka and Uyeda 1999;Shinoda and Uyeda 2002). A Baiu-frontal depression accompanied by a MaCS was generated in the downstream region of the Yangtze River on the night of 18 June 2001.…”
Section: Introductionmentioning
confidence: 99%